2016
DOI: 10.1002/anie.201602695
|View full text |Cite
|
Sign up to set email alerts
|

Supported Gold Nanoparticles for Efficient α‐Oxygenation of Secondary and Tertiary Amines into Amides

Abstract: Although the α-oxygenation of amines is a highly attractive method for the synthesis of amides, efficient catalysts suited to a wide range of secondary and tertiary alkyl amines using O2 as the terminal oxidant have no precedent. This report describes a novel, green α-oxygenation of a wide range of linear and cyclic secondary and tertiary amines mediated by gold nanoparticles supported on alumina (Au/Al2 O3 ). The observed catalysis was truly heterogeneous, and the catalyst could be reused. The present α-oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 47 publications
0
48
0
1
Order By: Relevance
“…Ther eaction proceeded smoothly when N,N-dimethylbenzylamine derivatives with electron-donating groups were used as the substrates,a nd the corresponding formamides were obtained in high yields (Table 3b, 15 and 16). Although N,N-dimethylbenzylamine derivatives with electron-withdrawing groups were less effective,the oxygenation was almost complete when the reaction time was increased to 24 h ( Table 3b, [17][18][19][20][21][22]. They ields of formamides were unsatisfactory with some kinds of N,N-dimethylamines,s uch as N,N-dimethylisopropylamine and N,N-dimethylbutylamine,u nder the standard conditions.F or these substrates, the corresponding formamides were obtained in good yields by using 2,4,4-trimethyl-2-oxazoline and increasing the amount of catalyst as with 1-methylpyrrolidine (Table 3b, 23 and 24).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Ther eaction proceeded smoothly when N,N-dimethylbenzylamine derivatives with electron-donating groups were used as the substrates,a nd the corresponding formamides were obtained in high yields (Table 3b, 15 and 16). Although N,N-dimethylbenzylamine derivatives with electron-withdrawing groups were less effective,the oxygenation was almost complete when the reaction time was increased to 24 h ( Table 3b, [17][18][19][20][21][22]. They ields of formamides were unsatisfactory with some kinds of N,N-dimethylamines,s uch as N,N-dimethylisopropylamine and N,N-dimethylbutylamine,u nder the standard conditions.F or these substrates, the corresponding formamides were obtained in good yields by using 2,4,4-trimethyl-2-oxazoline and increasing the amount of catalyst as with 1-methylpyrrolidine (Table 3b, 23 and 24).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[20] ii)Iminium cation intermediates produced by oxidation at the amethyl groups are thermodynamically unstable compared with the multi-substituted iminium cations.P reviously,w e reported that cyclic and linear a-methylene positions are selectively oxygenated in aerobic a-oxygenation of tertiary amines catalyzed by supported gold nanoparticles. [21] iii)Unlike cross-dehydrogenative coupling, a-oxygenation requires additional oxidation of hemiaminal intermediates,p roduced by hydration of the iminium cations.Wepreviously developed regioselective a-cyanation and a-alkynylation at N-methyl positions of tertiary amines by MnO 2 -based catalysts. [6,7] However,aMnO 2 -catalyzed methyl-selective a-oxygenation strategy failed because of the poor catalytic activity of MnO 2 for the hemiaminal oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…以 1a (10 g, 50.7 mmol)作底物, 氟硼酸锌水合物(1.7 g, 5.0 mmol, 10 mol%)为催化剂, 乙腈(100 mL)作为溶剂, 100 ℃回流反 与已报道的锌催化酮与盐酸羟胺的一步法反应体 系相比 [20,22] , 本体系反应条件较温和、 催化剂廉价易得、 产物收率高, 为酮与盐酸羟胺的一步法贝克曼重排反应 提供了一种"锌"方法. [23] 、 1b [25] 、 1c [25] 、 1d [26] 、1e [23] 、1f [23] 、1g [23] 、1h [23] 、1i [23] [28] 、2b [25] 、2c [25] 、2e [29] 、2f [30] 、2g [30] 、2h [30] 、 2i [31] 、2j [32] 均与文献报道中核磁数据相符. …”
Section: G 级贝克曼重排反应unclassified
“…15,40,41 Tertiary amine is the hydrophilic head group of MDH. Therefore, it is likely that MLP delivery of siPLK1 would increase uptake of siPLK1 by tumor cells.…”
Section: Intracellular Uptake Of Mlp/sirna By C6 Cellsmentioning
confidence: 99%